JAG1 and COL1A1 polymorphisms and haplotypes in relation to bone mineral density variations in postmenopausal Mexican-Mestizo Women - Rojano-Mejía, David (Springer Netherlands, 2011)
Osteoporosis is characterized by low bone mineral density (BMD). One of the most important factors that influence BMD is the genetic contribution. The collagen type 1 alpha 1 (COL1A1) and the JAGGED (JAG1) have been investigated in relation to BMD. The aim of this study was to investigate the possible association between two single-nucleotide polymorphisms (SNPs) of COL1A1, their haplotypes, and one SNP of JAG1 with BMD in postmenopausal Mexican-Mestizo women. Seven hundred and fifty unrelated postmenopausal women were included. Risk factors were recorded and BMD was measured in lumbar spine, total hip, and femoral neck by dual-energy X-ray absorptiometry. DNA was obtained from blood leukocytes. Two SNPs in COL1A1 (rs1800012 and rs1107946) and one in JAG1 (rs2273061) were studied. Real-time PCR allelic discrimination was used for genotyping. The differences between the means of the BMDs according to genotype were analyzed with covariance. Deviations from Hardy–Weinberg equilibrium were tested. Pairwise linkage disequilibrium between single nucleotide polymorphisms was calculated by direct correlation r(2), and haplotype analysis of COL1A1 was conducted. Under a dominant model, the rs1800012 polymorphism of the COL1A1 showed an association with BMD of the lumbar spine (P = 0.021). In addition, analysis of the haplotype of COL1A1 showed that the G–G haplotype presented a higher BMD in lumbar spine. We did not find an association between the s1107946 and rs2273061 polymorphisms of the COL1A1 and JAG1, respectively. Our results suggest that the rs1800012 polymorphism of the COL1A1, in addition to one haplotype, were significantly associated with BMD variation in Mexican-Mestizo postmenopausal women.